2020
DOI: 10.24252/idaarah.v4i1.13893
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Pendidik Dan Tenaga Kependidikan Dalam Meningkatkan Mutu Pendidikan

Abstract: The purpose of this research is to reveal the activity of management realization and personel education and find an effort done to increase the quality education by education management and personel education. The kind of this research is descriptive qualitative research in Al-Mansur Biangloe boarding school Bantaeng regency. Data collection methods by interview, observation and documentation. The result of research show that the implementation educator management and personel education at palnning step, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
19

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 1 publication
0
7
0
19
Order By: Relevance
“…However, this result supports research (Krisnawati & Bagia, 2021) (Rosmaini & Tanjung, 2019) which says that competence does not have a significant effect on employee performance due to the lack of knowledge possessed by employees, with this problem competence can be improved by attending trainings that are in accordance with their field of work, so that employees can deepen their knowledge and knowledge and can complete work well and improve their performance. Further research with the same results by Rahim (Nurlindah et al, 2020) concluded that the good competencies possessed by employees were not able to improve employee performance, it was found that some technical positions in the place of employees who did not have competence, this could be caused by discrepancies in position placement in accordance with the majors owned by employees. Research that also shows the same results, namely competence does not have a significant effect on employee performance, is also described in the results of research conducted by (Dhermawan et al, 2012), therefore Competence must be improved in order to improve employee performance.…”
Section: Measurement Model Evaluation (Outer Model)mentioning
confidence: 79%
“…However, this result supports research (Krisnawati & Bagia, 2021) (Rosmaini & Tanjung, 2019) which says that competence does not have a significant effect on employee performance due to the lack of knowledge possessed by employees, with this problem competence can be improved by attending trainings that are in accordance with their field of work, so that employees can deepen their knowledge and knowledge and can complete work well and improve their performance. Further research with the same results by Rahim (Nurlindah et al, 2020) concluded that the good competencies possessed by employees were not able to improve employee performance, it was found that some technical positions in the place of employees who did not have competence, this could be caused by discrepancies in position placement in accordance with the majors owned by employees. Research that also shows the same results, namely competence does not have a significant effect on employee performance, is also described in the results of research conducted by (Dhermawan et al, 2012), therefore Competence must be improved in order to improve employee performance.…”
Section: Measurement Model Evaluation (Outer Model)mentioning
confidence: 79%
“…Sumber daya manusia (SDM) pendidikan merupakan seluruh manusia yang terlibat dalam aktivitas pendidikan yang mempengaruhi kegiatan manajemen dalam organisasi. SDM pendidikan tersebut terdiri dari pimpinan, kepala sekolah/madrasah, guru/pendidik, peserta didik, tenaga administrasi dan lain sebagainya (Nurlindah et al, 2020).…”
Section: Pengaruh Pengelolaan Pendidikan Terhadap Manajemen Pendidika...unclassified
“…SDM pendidikan menjadi faktor penting dalam menjalankan manajemen pendidikan, dengan kontribusinya dalam penyelenggaraan pendidikan dapat menciptakan manusia yang bermutu. Pendidik dan tenaga kependidikan sebagai salah satu sumber daya manusia merupakan tenaga yang memegang peran penting dan strategis terutama dalam upaya meningkatkan mutu pendidikan, karena pendidik dan tenaga kependidikan kesehariannya secara langsung berinteraksi dengan peserta didik (Nurlindah et al, 2020).…”
Section: Pengaruh Pengelolaan Pendidikan Terhadap Manajemen Pendidika...unclassified
See 1 more Smart Citation
“…The results of research at Akbid An Nur Husada Walisongo show that the supervision and assessment by the Director as an internal supervisor is carried out periodically in one semester. The success of the monitoring process is determined by a detailed assessment that can provide feedback in the form of a clear picture of the level of success in achieving the goals and objectives that have been set [15]. It is also said that performance appraisal or performance evaluation is an assessment that is carried out systematically to find out the results of employee work and organizational performance.…”
Section: E Supervision and Performance Appraisalmentioning
confidence: 99%